Aflatoxins and fumonisins in rice and maize staple cereals in Northern Vietnam and dietary exposure in different ethnic groups. (December 2016) - Huong, Bui Thi Mai; Tuyen, Le Danh; Do, Tran Thanh; Madsen, Henry; Brimer, Leon; Dalsgaard, Anders
Abstract: Mycotoxins in food are increasingly a food safety hazard concern in particular in developing countries. This study was performed to determine the occurrence and determinants of aflatoxin and fumonisin contamination in rice and maize and to assess health risks through dietary intake exposure among ethnic minority groups in northern Vietnam. A total of 111 rice and 102 maize samples, were tested for occurrence of fungi and mycotoxins, i.e. aflatoxins (AF's) and fuminisin B (FB). Results showed that 107 (96.4%) rice and 84 (82.4%) maize samples were contaminated by fungi. Aspergillus flavus was found in 68 (61.3%) rice and 30 (29.4%) maize samples, Aspergilus parasiticus in 40 (36.0%) rice and 27 (26.7%) maize samples. AF's - were detected in 27 rice (24.3%) and 27 maize samples (26.4%) at minimum and maximum levels in rice of 2.06 and 77.8 ng/g and 20.5 and 110 ng/g in maize, respectively. Nine (8.1%) rice and 24 (23.5%) maize samples contained FB at ranges of 2.3–624 ng/g in rice and 5.6–89.8 ng/g in maize. Data collected through interviews and observations in households showed that type of crop, storage duration and presence of fungi, particularly mycotoxigenic fungi were important risk factors for AF's and FB contamination. Based on daily food consumption data, the estimated average exposure dose of aflatoxin B1 (AFB1 ) from rice was 21.7 ng/kg bw/day for adults and 33.7 ng/kg bw/day for children. For FB, the rice based average exposure amounted to 536 ng/kg bw/day for adults and 1019 ng/kg bw/day for children. The calculated excess risk of liver cancer incidence by ingestion of cereals containing AFB1 was 1.5 per 100, 000 adults and 2.3 per 100, 000 children per year. The average intake of FB was calculated to be lower than the tolerable diet intake (TDI). Our findings highlight that rice and maize are contaminated with mycotoxins at levels representing actual health hazards for the ethnic minority groups consuming these stable cereals. Proper drying and storage conditions in households are likely to reduce the mycotoxin contamination. Highlights: Crop type, storage and fungi are risk factors for AFB and FB1 contamination of rize and maize. AFB1 liver cancer risks was 1.5 per 100, 000 adults and 2.3 per 100, 000 children per year. Average intake of FB1 was lower than the tolerable diet intake (TDI) but still very high.